2023
DOI: 10.1111/1759-7714.14932
|View full text |Cite
|
Sign up to set email alerts
|

Predictive scoring of high‐grade histology among early‐stage lung cancer patients: The MOSS score

Abstract: Background: Poor prognosis associated with adenocarcinoma of International Association for the Study of Lung Cancer (IASLC) grade 3 has been recognized. In this study we aimed to develop a scoring system for predicting IASLC grade 3 based before surgery. Methods: Two retrospective datasets with significant heterogeneity were used to develop and evaluate a scoring system. The development set was comprised of patients with pathological stage I nonmucinous adenocarcinoma and they were randomly divided into traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
0
1
Order By: Relevance
“…The studies of Ryo and Wongi showed that males, younger patients and smokers were more likely to suffer from IASLC grade 3 tumors. 28 Different from Ryo’s study, our study found that more IASLC grade 3 tumors occurred in older patients. The biological characteristics of tumors might be more easily exhibited on imaging modalities.…”
Section: Discussioncontrasting
confidence: 85%
“…The studies of Ryo and Wongi showed that males, younger patients and smokers were more likely to suffer from IASLC grade 3 tumors. 28 Different from Ryo’s study, our study found that more IASLC grade 3 tumors occurred in older patients. The biological characteristics of tumors might be more easily exhibited on imaging modalities.…”
Section: Discussioncontrasting
confidence: 85%